Pelatihan Analisa Laporan Keuangan pada Karyawan PT Sinar Hidup Kota Medan, Sumatera Utara - Partogian Sormin; Yenni Yenni (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Financial Report is very important in the company because it is a fundamental thing that must be analyzed in the company for the continuity of the company. PT Sinar Hidup is a company engaged in the electronics sector. This company has prepared financial reports but needs a deeper explanation regarding the analysis of the results of these reports, especially to employees in the company. Employees also need the ability to analyze because it is fundamental and can be useful for decision making, including for decision making. Financial ratios can be used for making decisions in terms of profit, liquidity, cash flow, and also for debt. Employees are trained to be able to translate the meaning of ratios and financial analysis contained in the company's financial statements so that they can be precise in making Financial Reports, which are brief reports on a summary of financial results, including the financial position of a company. The financial statements of a company include balance sheets, profit and loss and cash flows from the company. Financial statements are very important because they are fundamental things that must be analyzed in the company for the continuity of the company. PT SInar Hidup is a company engaged in the electronics sector. This company has prepared financial reports but needs a deeper explanation regarding the analysis of the results of these reports, especially to employees in the company. Employees also need the ability to analyze because it is fundamental and can be useful for decision making, including for decision making. Financial ratios can be used for making decisions in terms of profit, liquidity, cash flow, and also for debt. Employees are trained to be able to translate the meaning of ratios and financial analysis contained in the company's financial statements so that they can be precise in making decisions.